In the shadow of the state: The informal economy and informal economy labor force - Friedrich Schneider (DANUBE: Law, Economics and Social Issues Review, 2014)
In this paper, the main focus lies on the informal economy and on work in the shadow. The most influential factors on the informal economy are tax policies and state regulation. The size of the informal economy was decreasing over the period 1999 to 2007, from 34.0% to 31.2% for 161 countries (unweighted average). Furthermore, economic opportunities, taxes and regulations, the general situation on the labor market, and unemployment are crucial for an understanding of the dynamics of the shadow labor force. In contrast with the decrease of the informal economy (value added figures), the informal economy labor force increased for most countries over the period 1999 to 2007.
Keywords: 330; Informal Economy; Undeclared Work; Shadow Labor Force; Tax Morale; Tax Pressure; State Regulation; Labor Market